Effects of Dietary Energy Profiles on Energy Metabolic Partition and Excreta in Songliao Black Pigs Under Different Ambient Temperature - Kai Zhou; Dan Jiang; Xiaogang Yan; Guixin Qin; Dongsheng Che; Rui Han; Hailong Jiang (Animals)
In order to further reveal the special characteristics of energy metabolism and the characteristics of energy requirements of fattening pigs grown in low-temperature environments, this study used a 2 × 2 × 2 factorial array of treatments, which harnessed two temperatures (low-temperature, LT group: 10 °C; normal-temperature, NT group: 20 °C), two feed energy levels (normal-energy, NE group: 14.02 MJ/kg metabolic energy; high-energy, HE group: 15.14 MJ/kg metabolic energy), and two feed energy sources (LF group: low fat, HF group: high fat). Thirty-two Songliao black fattening pigs with an initial body weight of 85.48 ± 2.31 kg were completely randomized into eight treatment groups, with four replicates in each treatment group and one pig in each replicate. The pigs were placed in a respiratory metabolic chamber for a 6-day trial. There was one pig per respiratory metabolic chamber in a single cage. The results showed that the average daily weight gain in the normal-temperature, high-energy, and high-fat groups was higher than that of the low-temperature, normal-energy, and low-fat groups (p < 0.05). The fat deposition rate, protein oxidation, and fat oxidation of the high-fat group were higher than those of the low-fat group (p < 0.05). The energy digestibility, protein digestibility, and fat digestibility in the high-fat group were higher than those in the normal-energy group (p < 0.05). The fat digestibility and energy deposition rate in the high-fat group were higher than those in the low-fat group (p < 0.05). The respiratory quotient in the high-energy group was lower than that in the normal-energy group (p < 0.05), and the respiratory quotient in the high-fat group was lower than that in the low-fat group (p < 0.05). There was an interaction between temperature and energy sources in terms of the respiratory quotient, fat oxidation, blood urea nitrogen content, and glucose content (p < 0.05). Appropriately increasing the energy level of the diet and improving the energy structure of the feed (increasing the level of fats and oils) will benefit Songliao black fattening pigs by increasing their energy use efficiency and at the same time reducing greenhouse gas CO2 emissions, and these changes are more pronounced in cold environments.